Economic impact and usage of urban green spaces in Kuala Lumpur, Malaysia - A. Samad, Nur Syafiqah (2019)
Almost half of the public urban green spaces (UGS) have been replaced with various forms of development. The quality and amenity value of UGS have slowly diminished, hence discouraging people from using UGS. This happens because the economic value of UGS is not properly valued. In order to overcome the problem of UGS loss, the government has taken numerous efforts including introducing green building (GB) practices which is mostly applicable for developers. However, only 8% out of 2,000 developers are actively involved with GB practice. Majority of them are not interested and state that GB practice is not a preferred investment for their business. The first objective of this study is to investigate the factors influencing the use of UGS in Kuala Lumpur (KL). A total of 15 public UGS within eight sub-districts in KL were covered in this study, while structural equation modelling and socio-ecological model were used to achieve the objective. The results show that physical environment is the most influential factor in the use of UGS in KL. Therefore, urban planner should improve the physical environment of existing UGS. The second objective is to estimate the economic value of UGS in KL using hedonic price method (HPM). In 2016, 1,269 house units were analysed. The HPM was regressed using ordinary least square (OLS) regression and geographically weighted regression (GWR). Based on the OLS regression, only five UGS (Taman Botani Perdana, Taman Rimba Kiara, Taman Datuk Keramat, Taman Ampang Hilir, and Hutan Simpan Bukit Nanas) were statistically significant with a negative sign. The marginal implicit prices for the five significant UGS were RM30,000, RM170,000, RM40,000, RM160,000, and RM90,000. Based on the GWR, all of the environmental attribute variables were significant except the size of Hutan Simpan Bukit Sg. Putih. Hence, the government should consider new policies related to quit-rent by imposing 5%-10% higher than the current quit-rent for the properties located within 1km from the UGS. The third objective is to evaluate the impact of GB practice on the firms’ financial performance. A total of 323 firms’ financial reports for the year 2015 were collected. Using propensity score matching (PSM) technique, it was found that firms with GB certificate had higher return on asset (ROA) compared to firms without GB certificate. In this case, the government could introduce new policies related to the requirements of business loan such as lower interest rate to help and encourage more firms to be involved with GB practice. In short, this study recommends several policies to be considered by the policy makers, local authorities, and property developers particularly on the UGS management and the implementation of GB practice.